Prevalence and risk factors of active hepatitis C infection among at-risk migrant populations in Madrid, Spain, 2019 to 2023 - Salvador Resino (Eurosurveillance)
BACKGROUND Hepatitis C virus (HCV) microelimination among at-risk migrants supports global elimination goals. AIM To evaluate risk factors, prevalence and trends of active HCV infection among at-risk migrants screened for HCV in Madrid from 2019–23. METHODS At-risk migrants (born outside Spain, living in country < 10 years regardless of legal status), were screened for HCV via mobile units with rapid antibody testing, and confirmed by RNA testing. Recruitment of this convenience sample focused on migrant centres, shelters, harm reduction centres and social service sites. Primary outcome was active HCV prevalence. Risk factors analysed included origin, alcohol use, no stable income, drug use and sexual behaviour. Data were analysed using general linear models with negative binomial distribution and p values adjusted for multiple comparisons (q values). RESULTS Among 2,288 migrants, 6.5% (149/2,288) had anti-HCV antibodies, 47.0% (70/149) of whom tested positive for HCV-RNA; 81.4% (57/70) began antiviral therapy. Overall prevalence of active HCV infection was 3.1% (70/2,288). Injection drug use (non-active vs never used (aIRR: 7.3; 95% CI: 2.7–12.7) and active (aIRR: 14.7; 95% CI: 6.7–32.1)), European origin (vs non-European; aIRR: 5.8; 95% CI:  2.7–12.7) and alcohol misuse (vs no misuse; aIRR: 1.8; 95% CI: 1.1–2.9) were main risk factors. Prevalence showed no significant change during 2019–23 in the overall population and across risk groups. CONCLUSION At-risk migrants screened in Madrid had a high prevalence of active HCV infection. This is higher than reported estimates for the general Spanish population and supports the need to enhance targeted HCV prevention, screening and treatment strategies among migrant populations.